2012
DOI: 10.1109/tasc.2011.2178579
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature and Magnetic Field Performance of Spliced Commercial YBCO CC

Abstract: The design of next-generation magnets based on 2G high-temperature superconductors requires a careful investigation of the possibilities and performance of joints between different superconducting wire pieces. In this paper, we present a study of the electrical performance of splices made with commercial Superpower ReBCO tapes at both 77 K and 4.2 K. For this study we developed a special splicing device based on the hot-bar soldering technique that allowed estimating the degree of reproducibility of the splici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…The range of R J values reported in the literature is large. The R J of similar soldered joints with the same CCs can vary from ∼4 to over 1000 nΩ cm 2 at 77 K [7,[34][35][36]. Inconsistent results are also found in the magnetic field dependence of R J .…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…The range of R J values reported in the literature is large. The R J of similar soldered joints with the same CCs can vary from ∼4 to over 1000 nΩ cm 2 at 77 K [7,[34][35][36]. Inconsistent results are also found in the magnetic field dependence of R J .…”
Section: Introductionmentioning
confidence: 85%
“…Inconsistent results are also found in the magnetic field dependence of R J . Some studies claimed that there was no observable field dependence of R J [7,36]. Other studies demonstrated that R J of the samples fabricated using the same kind of CCs changed significantly with an applied magnetic field [37].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, joints with sufficiently low resistance can be formed by simple soldering techniques for some applications such as power cables [9][10][11][12][13][14][15]. Joint resistance can be reduced below 10 −7 Ω when the superconducting layers in overlapped CC tapes are in closer proximity by removing other layers such as the Cu stabilizer, Ag cap layer, or solder material [5][6][7][8][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…8,9) While the length of NbTi wires could reach 10-15 km and 40-50 km for 0.5 T and 2.0 T magnets, respectively, the longest REBCO CCs with homogeneous I c reported so far are approximately 1 km, even in optimum fabrication conditions. 3,10,11) Several joint methods have been developed to lengthen REBCO CCs, such as use of a solder joint, 12,13) a diffusion joint using a metal stabilizer, [14][15][16] and a superconducting joint. [17][18][19][20] In the case of solder joints and diffusion joints, the presence of resistance is inevitable due to solders and stabilizers at the boundaries, which cause current loss and heat generation resulting in an inhomogeneous magnetic field.…”
mentioning
confidence: 99%